High pH reversed-phase preparative chromatographic separation of nadolol racemates using C18 adsorbents - Arafah, Rami (2020)
In recent years, the continuous improvement of preparative liquid chromatographic techniques, make easier the resolution of complex multicomponent chiral drugs, into single pure stereoisomers, by means of combining different strategies and using chiral and achiral adsorbents. Nadolol is one representative beta-blocker pharmaceutical drug prescribed worldwide for relieve of several diseases related with the cardiovascular system. This pharmaceutical chiral drug represents a very interesting case-study since it is composed by four stereoisomers, being a mixture of two racemates, i.e., a mixture of two pairs of enantiomers. The complete separation of all the four nadolol stereoisomers can be achieved using alternative strategies, different types of separation sequences and techniques, such as, the use of different adsorbents (chiral and achiral stationary phases), and the correspondent mobile phase optimization at both normal and reversed-phase modes [1-3]. In this work, a large set of experimental results will be presented for the separation of the two nadolol racemates using a commercial Azura preparative HPLC system, equipped with two 250 mL/min pump heads. The fixed-bed separation was carried out through a sequence of multiple injections, optimized by taking into account the retention time of both racemates using an XBridge Prep OBD C18 column with preparative dimensions (250mm ID x 30mm L) and with a particle size diameter of 10 m [4]. Experimental results will show the optimization of the mobile phase composition and injection time. The experimental results presented in this work stresses out the advantage of using a first achiral reversed-phase chromatographic separation step to perform the separation of the two nadolol racemates.